2020
DOI: 10.15296/ijwhr.2020.32
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Foeniculum vulgare Seed Extract on Fertility Results of Assisted Reproductive Technology in Women With Poor Ovarian Response

Abstract: Objectives: Foeniculum vulgare due to phytoestrogens is important in the treatment of female sexual dysfunction including infertility. Accordingly, this study was conducted to investigate the effect of the F. vulgare seed extract on the fertility results of assisted reproductive technology (ART) in women with a poor ovarian response (POR). Materials and Methods: In this before-after intervention, 19 infertile women with POR were enrolled by a convenience sampling method. T h e amounts of luteinizing hormone ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The extract has been shown to act as oxytocin, which has been antagonized by atropine [ 102 , 103 ]. Yavangi et al [ 104 ] found that F. vulgare seed extract administered orally was effective in improving the determinants of conception in women and could be used as a complementary therapy. The use of F. vulgare positively improved the quality of oocytes and fertility indices in women.…”
Section: The Importance Of Bioextracts In Females' Reproductive Systemmentioning
confidence: 99%
“…The extract has been shown to act as oxytocin, which has been antagonized by atropine [ 102 , 103 ]. Yavangi et al [ 104 ] found that F. vulgare seed extract administered orally was effective in improving the determinants of conception in women and could be used as a complementary therapy. The use of F. vulgare positively improved the quality of oocytes and fertility indices in women.…”
Section: The Importance Of Bioextracts In Females' Reproductive Systemmentioning
confidence: 99%